Development of electrospun, biomimetic tympanic membrane implants with tunable mechanical and oscillatory properties for myringoplasty. (1st April 2022) - Benecke, Lukas; Chen, Zhaoyu; Zeidler-Rentzsch, Ines; von Witzleben, Max; Bornitz, Matthias; Zahnert, Thomas; Neudert, Marcus; Cherif, Chokri; Aibibu, Dilbar
Abstract : The mechanical and oscillatory behavior of the biomimetic electrospun SF-PCL TM implants can be tuned by adjusting the solution concentration, the SF-PCL mixing ratio and the electrospinning parameters to achieve comparable properties to human TMs. Abstract : Most commonly, autologous grafts are used in tympanic membrane (TM) reconstruction. However, apart from the limited availability and the increased surgical risk, they cannot replicate the full functionality of the human TM properly. Hence, biomimetic synthetic TM implants have been developed in our project to overcome these drawbacks. These innovative TM implants are made from synthetic biopolymer polycaprolactone (PCL) and silk fibroin (SF) by electrospinning technology. Static and dynamic experiments have shown that the mechanical and oscillatory behavior of the TM implants can be tuned by adjusting the solution concentration, the SF and PCL mixing ratio and the electrospinning parameters. In addition, candidates for TM implants could have comparable acousto-mechanical properties to human TMs. Finally, these candidates were further validated in in vitro experiments by performing TM reconstruction in human cadaver temporal bones. The reconstructed TM with SF–PCL blend membranes fully recovered the acoustic vibration when the perforation was smaller than 50%. Furthermore, the handling, medium adhesion and transparency of the developed TM implants were similar to those of human TMs.